Innovation among different classes of software development organizations. (3rd November 2017) - Gaskin, James; Berente, Nicholas; Lyytinen, Kalle; Rose, Gregory
Abstract: Software development organizations (SDOs) innovate in diverse ways. In this paper, based on an extensive review of innovation typologies, we develop a theory‐driven typology of SDO innovator classes. We theorize about the driving forces behind these classes, with specific attention given to knowledge‐based dispositions that relate to the SDO's knowledge‐based competencies in technology appropriation, technology generation, and network intensity within ecological niches. Through a survey of 136 SDOs, which adopted Internet technologies during 1995‐2006, we empirically verify that these classes also determine different ways that SDOs innovate around software services they provide to their clients. Our findings suggest that the knowledge‐based dispositions of different SDO innovator classes impact how they innovate. Overall, the study involves theorizing around different types of innovation behaviours and associated knowledge‐based factors that influence the way SDOs innovate.